2016
DOI: 10.1016/j.carbpol.2016.06.098
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin- and starch-based hydrogels. Part A: Hydrogel development, characterization and coating

Abstract: The present work aims at constructing the ideal scaffold matrix of which the physico-chemical properties can be altered according to the targeted tissue regeneration application. Ideally, this scaffold should resemble the natural extracellular matrix (ECM) as close as possible both in terms of chemical composition and mechanical properties. Therefore, hydrogel films were developed consisting of methacrylamide-modified gelatin and starch-pentenoate building blocks because the ECM can be considered as a crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 60 publications
(64 reference statements)
5
52
0
Order By: Relevance
“…This technique was used to gain insight into the double bond conversion by quantifying the number of double bonds that were consumed during UV-induced crosslinking according to the protocol of Van Vlierberghe et al 31 A double bond conversion of around 95% for RCPhC1-MA was determined, while it was around 70% for Gel-MA. The latter result was in agreement with the double bond conversion of 63% for Gel-MA-based hydrogels reported earlier by Van Nieuwenhove et al 30 We hypothesize that the lower molecular weight of RCPhC1-MA contributes to a higher mobility of the photo-initiator and the biopolymer resulting in a higher double bond conversion. Hydrogels are ideal candidates for tissue engineering applications because they can closely mimic the aqueous environment of the extracellular matrix (ECM).…”
Section: Gel Fraction and Swelling Experimentssupporting
confidence: 93%
See 1 more Smart Citation
“…This technique was used to gain insight into the double bond conversion by quantifying the number of double bonds that were consumed during UV-induced crosslinking according to the protocol of Van Vlierberghe et al 31 A double bond conversion of around 95% for RCPhC1-MA was determined, while it was around 70% for Gel-MA. The latter result was in agreement with the double bond conversion of 63% for Gel-MA-based hydrogels reported earlier by Van Nieuwenhove et al 30 We hypothesize that the lower molecular weight of RCPhC1-MA contributes to a higher mobility of the photo-initiator and the biopolymer resulting in a higher double bond conversion. Hydrogels are ideal candidates for tissue engineering applications because they can closely mimic the aqueous environment of the extracellular matrix (ECM).…”
Section: Gel Fraction and Swelling Experimentssupporting
confidence: 93%
“…The results showed that for the 5 w/v% as well as the 10 w/v% concentration, stable hydrogels were formed. The obtained results are in accordance with previous data reported by Van Nieuwenhove et al and Van Hoorick et al 27,30 The gel fraction results provided a first indication that the UV crosslinking was efficient. HR-MAS 1 H-NMR spectroscopy experiments were performed to further substantiate the latter observation.…”
Section: Gel Fraction and Swelling Experimentssupporting
confidence: 93%
“…Despite very good biological properties of gelatin, neat gelatin hydrogel cannot be used in biomedical applications without chemical cross‐linking due to its instability under physiological conditions and also poor mechanical properties. For this reason, some cross‐linking strategies have been introduced to construct gelatin hydrogel networks, so far . To the best of our knowledge, fabrication of a gelatin‐based dynamic hydrogel using a benzaldehyde derivative has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, the extracellular matrix (ECM) of mammals is composed of a mixture of polysaccharides, water, soluble factors for signaling and cell-adhesive proteins. Starch based-hydrogels are therefore, partially able to mimic the natural cells aqueous environment, and this is very important when the hydrogel is to be used in tissue-engineering applications [ 9 ]. Starch-based hydrogels have been fabricated from water-starch solutions by applying ultrahigh pressure (UHP) at different temperatures [ 10 ] or by crosslinking with different types of crosslinkers such epichlorohydrin [ 11 ] or ammonium zirconium carbonate [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The material was subsequently cured with a bifunctional thiol-crosslinker. However, in this work, the starch hydrogels without additives were not robust enough to be manipulated [ 9 , 33 ].…”
Section: Introductionmentioning
confidence: 99%